ACTUAL ISSUES OF PREPARING CHILDREN FOR SCHOOL IN THE FAMILY ON THE BASIS OF THE STANDARD OF PRESCHOOL EDUCATION AND UPBRINGING - Esonova Malakhat Akilovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article analyzes the actual issues of preparing children for school in the family based on the standard of preschool education and upbringing. Based on the conclusions drawn, proposals were developed.